Functional development and experiments of a specific robotic arm based on ROS - Chang, Jindong (Nanyang Technological University, 2022)
With the development of science and technology, robots are used in more and more areas. The control of robots is an important part among them. Nowadays, the control of robots in industrial production line is mostly on-line teaching and off-line programming. However, both of them are original and the efficiency is greatly low. The robots need teaching every time when the mission has a slight change. Therefore, how to control robots in an efficient way has become an important problem. Based on this problem, This dissertation develops functions for a specific robotic arm. The robotic arm could be controlled in a more efficient way to complete different missions. Besides, through the corporation of the camera and AprilTag, the robotic arm could realize intelligent pick and place. The specific research contents of this dissertation are as follows: (1) Through the analysis of mechanical structures of robotic arm, the spatial coordinate description and transformation of the robotic arm is realized. The kinematics and inverse kinematics of the robotic arm are completed. Besides, two methods of motion trajectory planning, including joint space planning and Cartesian space planning, are finished. (2) Based on ROS, the functions of robot arm is completed. The robotic arm could be controlled in Python API to finish motion trajectory planning. The simulation in Moveit and realistic opeartion are both completed. (3) By the corporation of the camera and AprilTag, the robot intelligent grasping is realized. The robotic arm could identify the target and get the accurate location of the target. If the target is in the range of robotic arm, it will start to pick and place it to the designated location. (4) By using the multi-machine communication mechanism of ROS, the same two robotic arms could complete sync mirroring work. This could be used in different areas such as collaborative handling.